Publishing Anglo-Caribbean Fiction. - Robinson-Walcott, Kimberly Anne (International Journal of the Book)
The birth of the West Indian novel took place in the 1950s, in London. The migration of anglo-Caribbean creative talent to the perceived cultural mecca of the mother country, combined with a growing intellectual interest in the newly independent ex-colonies by enlightened ex-colonists, combined — most critically — with UK publishers' recognition of potential new markets, led publishers such as Andre Deutsch to sign up new voices such as Lamming, Naipaul and Selvon. In the 70s the interest of UK publishers in West Indian fiction waned; and notwithstanding the sporadic appearance of works by West Indian novelists in the lists of US and Canadian publishing houses, an opportunity arose for West Indian publishers to fill the gap. A few took the plunge: in Jamaica, for example, Kingston Publishers launched a fiction list in 1983 and since then has published some 35 fiction titles, including 4 novels by Anthony Winkler. Winkler, however, recently signed with Macmillan UK, a company which has an ambitious new and forthcoming Caribbean fiction list, as does another UK publishing house, Peepal Tree Press. The publishing of Caribbean fiction, sadly (for those concerned about the development of Caribbean publishing), is returning to the metropole. Meanwhile, some titles published recently in the UK raise questions of authenticity. This paper explores the reasons for this return and the possible implications for Caribbean fiction.